Depression risks (Colombia Medica, 1990)
The presence of depressed patients at the general doctor's office is a common ocurrence. Unfortunately, the correct diagnosis is frequently missed, and treatments are inadequately carried out. These two common mistakes automatically increase human suffering both for the patient and his family and, even worse, make higher the risk of suicide.